A Survey of Short-Selling Regulations - Edwards, Amy K; Reed, Adam V; Saffi, Pedro A C (The Review of Asset Pricing Studies, 2024)
Abstract Given the complex and controversial nature of short-selling regulation, we review the academic literature and provide insights for policy makers and academics. We organize the complex history of short-selling regulation into three areas: trading restrictions, securities lending regulations, and disclosure requirements. We identify, analyze, and discuss 45 distinct regulations promulgated from 1896 to 2021, primarily by reviewing the academic literature and the data sources employed. We provide several insights regarding the effectiveness of regulatory approaches and the wider impact of short-selling regulation on markets. (JEL G2, G12, G14, G15, G34)